Nicholas Cusanus and His 'non-aliud' as Concept of God - Stoffers, Johannes (European journal for philosophy of religion, 2019)
This paper presents Cusanus' dialogue of 1462, named after and centred on the concept of non-aliud, and exploits its speculative resources for conceiving the relationship between God and the realm of finite entities. Furthermore, it points to the elements of self-constitution of the absolute and of the latter's grounding relation towards the contingent. Finally, it is argued that Cusanus' concept of non-aliud offers a valuable contribution to the present debate about an adequate concept of God.